Effect of Instrument-assisted Soft-tissue Mobilisation of Iliotibial Band with Conventional Exercise Therapy versus Conventional Exercise Therapy Alone on Clinical Performance in Patients with Knee Osteoarthritis: A Prospective Interventional Study - Janvhi Balbir Gandotra; Pranita Dattatraya Ganjave; Riddhi Ashish Shroff (Journal of Clinical and Diagnostic Research)
Introduction: Osteoarthritis (OA) of the knee is the second most prevalent rheumatological issue in India. Myofascial factors play a role in symptom presentation, challenging conventional perspectives on treatment. Instrument-assisted Soft-Tissue Mobilisation (IASTM) is used for treating soft-tissue injuries, but its impact on relieving the Iliotibial Band (ITB) and improving knee mobility in OA patients is still not well understood. Aim: To evaluate the impact of combining IASTM with conventional exercise therapy versus conventional exercise therapy alone on knee Range of Motion (ROM), pain, functional performance, and functional disability in patients with grade 1 and 2 knee OA. Materials and Methods: The present prospective interventional study was conducted in the Outpatient Department (OPD) of Physiotherapy, D. Y. Patil Hospital and Research Centre, Navi Mumbai, Maharashtra, India from September 2023 to February 2024. Total 40 participants with grade 1 and 2 knee OA, aged 45-60 years, were randomly assigned to the conventional and experimental groups. Pain intensity was assessed using a numerical pain rating scale, and knee flexion ROM was measured with a universal goniometer. Functional performance and functional disability were evaluated using the 30-second sit-to-stand test and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Centre for Rheumatic Disease (CRD) Pune version 10, respectively. Participants underwent sessions three times a week over a two-week period. Data was analysed using the Statistical Package for Social Sciences (SPSS) software version 16.0. Intergroup comparisons were carried out using either independent t-tests or Mann-Whitney U tests. Intragroup comparisons were performed using dependent t-tests or Wilcoxon matched pairs tests. A significance level of 1% was utilised. Results: Intragroup analysis showed that both the conventional group (mean age 53.80±5.51 years) and the experimental group (mean age 50.22±4.61 years) had statistically significant improvements in knee flexion ROM, pain, functional performance, and functional disability (p-value<0.05). The experimental group demonstrated statistically significant superior improvements in pain (p-value=0.0077*), knee flexion ROM (p-value=0.0007*), and functional disability (p=0.0006*) compared to the conventional group. However, the functional performance showed statistically significant equal improvement in both groups. Conclusion: Combining IASTM with conventional exercise therapy led to superior improvements in knee flexion ROM, pain reduction, and functional disability compared to conventional exercise therapy alone in individuals with knee OA. However, both interventions were equally effective in enhancing functional performance.